General Internal Medicine VI (Spring) - Torun, Cundullah; Cure, Osman; Cengiz, Kuddusi; İlkkılıç, Kadir and Algun, Ekrem and Donma, Mustafa Metin and Tuncer, Sibel Çiğdem and Altan, Nilgün and Dinçel, Aylin Sepici and Kosava, Funda and Engin, Atilla and Memiş, Leyla and Koca, Cemile and Kocamanoğlu, Nilgün and Yılmaz, Yusufcan and Mutlay, Feyza and Baydar, Mustafa and Yıldırım, Bülent and Kadiroğlu, Berfin and Kadiroğlu, Zehra (Academician Publishing Book DOI Portal, 2024)
-